Os dispositivos da violência escolar: o caso da Escola Municipal Higino Antunes Pires Neto - Tombini, Leila (2018)
The study analyzed how the school (direction, pedagogical coordination and teachers) develops its practices on school violence, as well as the mechanisms, devices, and strategies used to deal with violence. For that, the research was based on the theory of Michel Foucault (2016). Perspective that distinguishes power from the phenomenon of violence. This is because every institution, and with the school, is no different, it is characterized by power relations, and it is through the power relations that the mechanisms, the readings and the institutional strategies (the devices) that they manage, are triggered , with violence, in schools. In view of the above, we seek to study the phenomenon of violence through the device concept. A concept defined by Foucault (2016) as the articulation of heterogeneous knowledges with institutional practices involving said and unspoken, elaborated with the objective of answering the emergence of certain questions, in view of specific historical moments. The general objective was to analyze, from the consolidated devices in the Higino Antunes Pires Neto School, the knowledges and practices that turned to the issue of school violence. The specific objectives were, respectively, to understand the relations existing in postmodernity with the school institution, violence and power. Characterize the institution, approach and research procedures. To observe the constitutive elements of institutional practices in the Higino Antunes Pires Neto School in its relation to the construction of pedagogical strategies used in the face of school violence. The study was developed in the Line of Research Society, Knowledge and Education. From the methodological point of view, the dissertation was based on poststructuralism, especially in the genealogical perspective of Michel Foucault (2016). The research used as a method the case study and as research techniques the analysis of documents, interviews and questionnaires, which were carried out with students, teachers, pedagogical team and school management. The research resulted in nine devices, namely: CREAS Device, Directed Play Device, PROERD Device, Pedagogical Device, Disciplinary Device, Religious Device, Psychological / Medical Device, School Patrol Device and Device Council Guardianship. These devices were created according to the emergence of the phenomenon of violence in the institution, and they acted in the control of the behavior of the entire school community. The research also pointed to the point of resistance presented before the devices, which obliged the School to rearticulate its practices, in order to reach those who do not fit the proposed format / behavior. In this way, the institutional devices unleashed of the School researched, in a certain historical moment, and directed to the confrontation of violent actions.